Glomerular Endothelial Cell Crosstalk With Podocytes in Diabetic Kidney Disease - Mahtal, Nassim; Lenoir, Olivia; Tharaux, Pierre-Louis (Frontiers in Medicine, 2021)
Diabetes is the main cause of renal failure worldwide. Complications of the kidney micro-and macro-circulation are common in diabetic patients, leading to proteinuria and can progress to end-stage renal disease. Across the complex interplays aggravating diabetes kidney disease progression, lesions of the glomerular filtration barrier appear crucial. Among its components, glomerular endothelial cells are known to be central safeguards of plasma filtration. An array of evidence has recently pinpointed its intricate relations with podocytes, highly specialized pericytes surrounding glomerular capillaries. During diabetic nephropathy, endothelial cells and podocytes are stressed and damaged. Besides, each can communicate with the other, directly affecting the progression of glomerular injury. Here, we review recent studies showing how in vitro and in vivo studies help to understand pathological endothelial cells-podocytes crosstalk in diabetic kidney disease.